Ethanol-induced apoptosis in hepatoma cells proceeds via intracellular Ca2+ elevation, activation of TLCK-sensitive proteases, and cytochrome c release - Nakayama, Nobuaki; Müller-Schilling, Martina; Krammer, Peter H. (Experimental cell research, 2001)
Ethanol is known to induce apoptosis in hepatocytes. However, intracellular signaling events of ethanol-induced death are still only partially understood. We studied such processes in ethanol-induced apoptosis in HepG2 cells as a model system for human liver cells. We determined the incidence of apoptosis by DNA fragmentation and tested the effects of various known inhibitors. Ethanol induces apoptosis in HepG2 cells in a dose- and time-dependent manner as well as in rat primary hepatocytes. This effect was not mediated through the death receptor CD95 and the tumor necrosis factor receptors. It was efficiently inhibited by the caspase inhibitor N-benzyloxycarbonyl-Asp-Glu-Val-Asp-fluoromethylketone (zVAD-fmk), the Ca2+ chelator EGTA, and the serine protease inhibitor N-p-tosyl-l-lysine chloromethyl ketone (TLCK). Upon ethanol treatment, the intracellular calcium ion concentration was increased and cytochrome c was released from the mitochondria, and caspases were activated. EGTA and TLCK could inhibit cytochrome c release from the mitochondria. Furthermore, overexpression of Bcl-xL saved cells from ethanol-induced apoptosis. These data suggest that ethanol-induced apoptosis in liver cells is initiated by the intracellular Ca2+ elevation in the cytoplasm and activation of TLCK-sensitive serine proteases. Our data provide new insight into ethanol-induced apoptosis in liver cells and may lead to therapeutic strategies to prevent liver damage.